PENINGKATAN PRESTASI BELAJAR SISWA DALAM MENGGAMBAR MELALUI PENGGUNAAN MEDIA PUZZLE MULTIFUNGSI BAGI SISWA SMP NEGERI 12 KOTA BIMA - Supriadi (BBPPMPV Seni dan Budaya Yogyakarta, 2021)
Young teens at the age of 12-14 years old are in the pseudo-naturalism development phase of drawing. At the range of the respective ages they are already able to draw by having attention to details, understanding the concept of space, and producing drawings that look realistic. As a matter of fact, the eight graders’ drawing works at SMP Negeri 12 Kota Bima have not yet demonstrated the result of the expected target on that phase. Classroom action research was conducted to fnd out about the problem and to help students increase the quality of their drawing. The improvement of students’ learning achievement in drawing using multifunction puzzle media in the learning process was investigated in the current classroom action research. The subjects of the research were the eight graders of Class VIII-A in SMP Negeri 12 Kota Bima in the academic year of 2016/2017. Data were collected using assignment test method. The learning achievement in drawing increases quantitatively if students can achieve the minimum class average score of 75. The result of the research demonstrates that students’ scores increase significantly after experiencing the learning process using multifunction puzzle media. The average students’ score increased from 72.58 in cycle 1 to 78.33 in cycle 2